Quantitative Analysis of Nuclear Lamins Imaged by Super-Resolution Light Microscopy - Kittisopikul M; Virtanen L; Taimen P; Goldman RD (MDPI, 2022)
The nuclear lamina consists of a dense fibrous meshwork of nuclear lamins, Type V intermediate filaments, and is similar to 14 nm thick according to recent cryo-electron tomography studies. Recent advances in light microscopy have extended the resolution to a scale allowing for the fine structure of the lamina to be imaged in the context of the whole nucleus. We review quantitative approaches to analyze the imaging data of the nuclear lamina as acquired by structured illumination microscopy (SIM) and single molecule localization microscopy (SMLM), as well as the requisite cell preparation techniques. In particular, we discuss the application of steerable filters and graph-based methods to segment the structure of the four mammalian lamin isoforms (A, C, B1, and B2) and extract quantitative information.